Current instability phenomena in a tunnel diode and electron self-organization processes - L.V. Chirkova; K.T. Ermaganbetov; K.M. Makhanov; K.S. Rozhkova; E.T. Arinova; A. Kurmash (Қарағанды университетінің хабаршысы. Физика сериясы)
In the article the mechanisms of electric instability in semiconductors are considered. The origin of negative differential conductivity of different types are described. On the example of functioning of the tunnel diode the mechanism of formation of the concentrated instability in semiconductors resulting in N-shaped voltampere characteristic of the diode is considered. It is shown that the «semiconductor structure consisting of two layers of semiconductors with different type of conductivity and an external source of electric energy» system can be considered as an open non-equilibrium thermodynamic system in which self-organization processes are possible. Operation of the tunnel diode in terms of the theory of self-organization in semiconductor structures is analysed. Processes of self-organization are resulted by change of concentration of carriers of a charge in power zones of p- and n-semiconductors of types which make the tunnel diode and therefore the direction of streams of electrons changes. The description of the movement of carriers of a charge in the considered semiconductor structure at various values and external shift is given: in an equilibrium state, at the return shift; at the direct shift and tension which have values less peak value; and tension exceeding «voltage dip». In a thermodynamic non-equilibrium system there can be processes of self-organization of various nature — tunneling and injection of electrons. At the same time the direction of processes of self-organization is defined by features of power ranges of the semiconductors making the tunnel diode and intensity of interaction between system elements.